Effects of high-grain or high-roughage transition diets on finishing performance of cattle previously fed high-concentrate growing diets - Sean P. Montgomery; J.J. Sindt; T.B. Farran; H.J. LaBrune; R.D. Hunter; James J. Higgins; T.A. Nutsch; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
Three hundred twenty-eight crossbred beef steers previously fed high-concentrate growing diets had ad libitum access to one of two transition diets prior to initiation of the finishing phase. Transition diets consisted of 58% steam-flaked corn and 30% alfalfa hay or of 23% steamflaked corn and 65% alfalfa hay (DM basis). Average daily gains, dry matter intakes, and feed efficiencies during the transition phase were greater for steers fed the high-grain diet than for steers fed the high-roughage diet (P.20).
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Transition Diet; Grain; Roughage; Finishing cattle